A Class of q-ary 2-IPP Codes - Batra, Sudhir; Singh, Parvinder (Journal of Informatics and Mathematical Sciences, 2013)
Sufficient conditions in terms of distance for the existence of binary 2-frameproof codes are obtained. A new class of q-ary 2-IPP codes has been explicitly constructed using latin square designs.